2021
DOI: 10.3389/fnmol.2021.638176
|View full text |Cite
|
Sign up to set email alerts
|

The Val66 and Met66 Alleles-Specific Expression of BDNF in Human Muscle and Their Metabolic Responsivity

Abstract: Brain-derived neurotrophic factor (BDNF) plays an essential role in nervous system formation and functioning, including metabolism. Present only in humans, the “Val66Met” polymorphism of the BDNF gene (BDNF) is suggested to have a negative influence on the etiology of neurological diseases. However, this polymorphism has only been addressed, at the molecular level, in nonhuman models. Knowledge about Val66- and Met66-variant differences, to date, has been achieved at the protein level using either cell culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…In the first in situ study identifying a difference in the allele-specific expression of the BDNF containing the Val66met polymorphism, a decrease in the expression levels of BDNF was shown in individuals heterogenous for the Val66met polymorphism, which is not detected in circulating blood [24]. This is consistent with the available clinical studies to date that have been unable to demonstrate a relationship between the presence of the Val66met polymorphism and alterations in circulating BDNF concentrations [25][26][27][28].…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…In the first in situ study identifying a difference in the allele-specific expression of the BDNF containing the Val66met polymorphism, a decrease in the expression levels of BDNF was shown in individuals heterogenous for the Val66met polymorphism, which is not detected in circulating blood [24]. This is consistent with the available clinical studies to date that have been unable to demonstrate a relationship between the presence of the Val66met polymorphism and alterations in circulating BDNF concentrations [25][26][27][28].…”
Section: Introductionsupporting
confidence: 75%
“…There has only been one study to date that has humans [24]. Considering that this study was very Their study showed a lower depolarization induced BDNF release, with no effects on the constitutive secretion system in Met66BDNF transfected neurons.…”
mentioning
confidence: 62%
“…It is important to address that the vast majority of studies investigating the Val66- and Met66-variant differences at the protein level have used animal models or cell cultures [ 93 ]. Results from a human study indicated that metabolic stress downregulates the expression of BDNF but not concentrations of plasma BDNF [ 93 ]. An alteration in the pro-BDNF/BDNF ratio deriving from the rs6265 polymorphism might be important to consider [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to rodents, the effect of PE on neurotrophin synthesis in human skeletal muscle has also been studied (Matthews et al, 2009;Walsh et al, 2014;de Assis et al, 2021). Nevertheless, in humans, only the acute PE paradigm has been studied.…”
Section: The Bdnf Gene Structure and Bdnf Expression In Skeletal Musclementioning
confidence: 99%
“…This response can result from a delayed muscle response in gene expression (Louis et al, 2007;Walsh et al, 2014). Other evidence suggests a significant reduction of mRNA Bdnf levels after a graded and maximal exercise test (de Assis et al, 2021). Acute metabolic stress caused by exhaustive PE was the main factor to explain the decay in Bdnf expression (de Assis et al, 2021).…”
Section: The Bdnf Gene Structure and Bdnf Expression In Skeletal Musclementioning
confidence: 99%